LATERAL APPROACH OF POPLITEAL BLOCK VERSUS UNILATERAL SPINAL ANESTHESIA FOR BELOW KNEE SURGERIES: A COMPARATIVE STUDY - Pujari, Mayura D; Kakade, Pooja D; Benare, Aparna G (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aims of the study were to compare efficacy and side effects of popliteal block and unilateral spinal anesthesia in patients undergoing below knee surgeries. Methods: This was a comparative study comprising patients undergoing below knee surgeries. Sixty patients were divided into two groups depending on whether surgery was done under unilateral spinal anesthesia (Group SA) or popliteal block (Group PB). The parameters compared between the studied groups included hemodynamic changes, onset of motor block, onset and duration of analgesia, duration of motor block, onset of pain, and amount of rescue analgesia required. Side effects such as bradycardia, hypotension, cardiac arrhythmia, and urinary retention were compared between the two groups. SSPS 22.0 was used for statistical analysis and p<0.05 was taken as statistically significant. Results: There were 14 (46.67%) males and 16 (53.33%) females, whereas, in Group PB, there were 13 (43.33%) males and 17 (56.67%) females. Mean age of patients in Group SA was found to be 42.93±16.79 and 39.57±14.05 in Group PB. The mean age and gender distribution and ASA grades of patients in both the groups were found to be comparable with no statistically significant difference. The mean duration of sensory as well as motor block was found to be significantly less in Group SA as compared to Group PB and the difference was statistically highly significant (p<0.001). Group PB showed a better hemodynamic as well as analgesic profile as compared to Group SA. The analgesic requirement in first 24 h was more in Group SA as compared to Group PB and the difference was statistically highly significant (p<0.001). Adverse effects in both the groups were comparable (p>0.05). Conclusion: Popliteal block provides better analgesia and hemodynamic stability as compared to unilateral spinal anesthesia and, hence, can be considered preferred mode of anesthesia in patients undergoing lower limb surgeries.v